PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) BERUPA REPLIKA BANGUN DATAR BERBANTUAN MEDIA RODA KUIS PUTAR UNTUK MENINGKATKAN KOLABORASI DAN HASIL BELAJAR SISWA - Velia Ayu Anurrohmah; Dede Nuraida; Ngunarti (STKIP Subang, 2026)
This Classroom Action Research (CAR) was motivated by low collaboration skills and mathematics learning outcomes regarding two-dimensional shape elements in a 3rd-grade elementary school, due to teacher-centered learning. Conducted in two cycles—each comprising planning, action, observation, and reflection—the study involved 25 students of Grade III B UPT SDN Kebonsari 3 Tuban. Data were collected via questionnaires, observation sheets, and interviews, then analyzed using descriptive quantitative and qualitative methods.The results showed that implementing the Project Based Learning (PjBL) model using two-dimensional shape replicas assisted by a Spinning Quiz Wheel significantly improved student collaboration and learning outcomes. Student mastery (MMC) escalated from 45% in the pre-cycle to 65% in cycle I, and reached 85% in cycle II. Additionally, students demonstrated greater enthusiasm, active participation, and better conceptual understanding.In conclusion, the PjBL model assisted by a spinning quiz wheel effectively improves students' collaboration skills and mathematics learning outcomes. This innovative model and media are highly recommended for other topics requiring active student engagement